1972
DOI: 10.1002/hlca.19720550402
|View full text |Cite
|
Sign up to set email alerts
|

Über die Synthese der Pilocarpus‐Alkaloide Isopilosin und Pilocarpin, sowie die absolute Konfiguration des (+)‐Isopilosins

Abstract: Soci6t6 suisse de chimie, B&le -Societ& svizzera di chimica, Basilea Nachdruck verboten -Tous droits rCservCs -Printed by Birkhauser AG., Basel, Switzerland Summary.A novel synthesis for rac-pilosinine (6 rac) and transformation of ( + )-pilosinine (6) into the pilocarpus alkaloids (+)-isopilosine (9) and (+)-pilocarpine (15) are described. By correlation via 6 with 15 the absolute configuration of (+)-isopilosinc (9) is established.Von den funf aus Pilocarpus-Arten isolierten Imidazol-Alkaloiden l), die teil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

1972
1972
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…1 C and D); 1tyrosine (δ 7.22 -H-2 and 6), 2 -β glucose (δ 4.58), and 3lactone ring (δ 4.18, H-8). compounds 6 (m/z 241) or 8 (m/z 285), as previously described in imidazole alkaloid synthesis [4]. In this study we have shown that NMR and MS are complementary techniques for the identification of different classes of metabolites in P. microphyllus.…”
Section: Compoundsupporting
confidence: 56%
See 1 more Smart Citation
“…1 C and D); 1tyrosine (δ 7.22 -H-2 and 6), 2 -β glucose (δ 4.58), and 3lactone ring (δ 4.18, H-8). compounds 6 (m/z 241) or 8 (m/z 285), as previously described in imidazole alkaloid synthesis [4]. In this study we have shown that NMR and MS are complementary techniques for the identification of different classes of metabolites in P. microphyllus.…”
Section: Compoundsupporting
confidence: 56%
“…P. microphyllus is economically the most important representative of jaborandi because it contains high concentrations of the imidazole alkaloid, pilocarpine, which is used to treat glaucoma as a stimulant of lachrymal and sweat glands and in the control of xerostomia [1]. In addition to pilocarpine, other imidazole alkaloids such as 3-nor-8 (11)-dihydropilocarpine, anhydropilosine, pilosine, and pilosinine have also been found in jaborandi leaf extracts [2][3][4][5]. However, of all these imidazole alkaloids produced in P. microphyllus, only pilocarpine has pharmaceutical applications.…”
mentioning
confidence: 99%
“…2) has high resolution mass and fragmentation compatible with dehydropilosinine, reported in the synthesis of pilocarpine proposed by Link and Bernauer (1972). This alkaloid was found in six of the species: P. carajaensis, P. spicatus, P. trachyllophus, P. pennatifolius, P. jaborandi and P. racemosus, indicating that it is also quite common in this genus.…”
Section: Alkaloid Profile In Different Speciesmentioning
confidence: 87%
“…Pilocarpus microphyllus is the species of the genus which accumulates the largest amount of pilocarpine in leaves and is found mainly in the Amazon region of Brazil (Pinheiro, 1997). In addition to pilocarpine, leaf extracts from this species also contain other alkaloids, such as 3-nor-8(11)-dihydropilocarpine, anhydropilosine and pilosine, pharmacological activity of which is still unknown (Andrade Neto et al, 1996;Link and Bernauer, 1972;Voigtlander, 1978). Similar to other species from this region, it has been extensively exploited and, as a result, it was included a few years ago in the list of Brazilian endangered plant spe-cies (Pinheiro, 1997).…”
Section: Introductionmentioning
confidence: 99%